Primary healthcare policy implementation in South Asia. Issue 2 (6th September 2016) - van Weel, Chris; Kassai, Ryuki; Qidwai, Waris; Kumar, Raman; Bala, Kanu; Prasad Gupta, Pramendra; Haniffa, Ruvaiz; Rajapaksa Hewageegana, Neelamani; Ranasinghe, Thusara; Kidd, Michael; Howe, Amanda
Abstract : Primary healthcare is considered an essential feature of health systems to secure population health and contain costs of healthcare while universal health coverage forms a key to secure access to care. This paper is based on a workshop at the 2016 World Organization of Family Doctors (WONCA) South Asia regional conference, where the health systems of Bangladesh, India, Nepal, Pakistan and Sri Lanka were presented in relation to their provision of primary healthcare. The five countries have in recent years improved the health of their populations, but currently face the challenges of non-communicable diseases and ageing populations. Primary healthcare should be a core component in restructuring health systems. However, there is a lack of understanding among policymakers of the unique contribution of primary healthcare to the health of populations. This results in insufficient investment in facilities and low priority of specialty training in the community setting. Regional collaboration could strengthen the advocacy for primary healthcare to policymakers and other stakeholders. Priorities were investment in community-based health facilities, and access to healthcare through professionals specialty-trained in the primary healthcare setting. This development fits the strategy of the WHO South East Asian Region to use community-based healthcare in achieving universal health coverage for the Asian populations.